An Exploratory Study on the Influence of Web 2.0 on the Digital Education of Socially Vulnerable Young People - Araújo, Fabricio O.; Araújo, Gilderlanio S.; Lima, Maria Cilene S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
This paper presents the results of an exploratory study with socially vulnerable youths with the aim of analyzing the implications of Web 2.0 to the digital education of these people. The methodology is based on a framework of practices in qualitative research. The results demonstrated that Web 2.0 has important implications along digital education process of youths who faces digital divide, enabling the development of informational capabilities of these individuals.